Інформаційна технологія поліноміального прогнозуючого контролю безвідмовної ро-боти технічних систем - Atamanyuk, I. P.; Kondratenko, Yu. P. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2013)
An information technology of estimating the probability of failure-free operation of technical systems in the future is received. The method is based on an algorithm of simulation of a posteriori nonlinear random sequence of the controlled parameter changes with the restricted membership of a range of possible values. The probability of trouble-free operation is defined as the ratio of the number of realizations, which are caught in the allowable range of the total number of them, formed in the result of numerical experiment. Implementation of a posteriori random sequence is an additive mixture of optimal in root mean square nonlinear assessment of the future value of the analyzed parameter, and the value of the random variable, which is impossible to predict, taking into account the stochastic nature of the parameter. The model of a posteriori random is based on Pugachev’s canonical decomposition. The proposed information technology does not impose any significant restrictions on the class of the random sequences (linear, stationary, Markov’s sequences, monotony, etc.). We also took into account the use of information technology only if the monitoring parameter is measured with errors.